Structure and stability of D-galactose/D-glucose-binding protein. The role of D-glucose binding and Ca ion depletion. Issue 3 (2010) - Stepanenko, Olga V.; Povarova, Olga I.; Stepanenko, Olesya V.; Fonin, Alexander V.; Kuznetsova, Irina M.; Turoverov, Konstantin K.; Staiano, Maria; D'Auria, Sabato
Abstract : The effects of guanidine hydrochloride (GdnHCl) on the structure and stability of the D-galactose/D-glucose-binding protein from Escherichia coli (GGBP) and its complex with D-glucose (GGBP/Glc) were investigated by intrinsic protein fluorescence and far-UV circular dichroism (CD). The role of calcium in the stability of the protein structure was also studied. It was shown that the processes of GGBP and GGBP/Glc unfolding induced by GdnHCl followed one-step reversible denaturation mechanism. The obtained data showed that the binding of glucose to GGBP resulted in an increase of the protein stability towards the actions of the GdnHCl which made protein unfolding more cooperative. The stabilities of GGBP alone, GGBP in the presence of glucose, GGBP-depleted calcium (GGBP-Ca), and GGBP/Glc-depleted calcium (GGBP/Glc-Ca) were characterized by difference of Gibbs free energies.